Composition dependence of piezoelectric constant and dielectric constant tunability in the < 001 >-oriented Pb(Mg1/3Nb2/3)O-3-PbTiO3 single crystals - Chew, Khian Hooi; Luo, H.S.; Zhao, X.Y.; Wang, J.; Yin, Z.W.; Chan, H.L.W.; Choy, C.L. (2004)
Composition dependence of room temperature piezoelectric constant d(33) and dielectric constant tunability was investigated in the (001)-poled single crystals of (1-x)Pb(Mg1/3Nb2/3)O-3-xPbTiO(3) with x varying from 0.24 to 0.38. Temperature, frequency and composition dependence of the dielectric constant in the unpoled crystals shows that the critical composition for the relaxor state lies in the 0.69Pb(Mg-1/3 Nb-2/3)O-3-0.31PbTiO(3) crystal. It has also the largest piezoelectric constant d(33) of 2210 pC/N and highest dielectric constant tunability of 40.6% (at a dc bias of 1000 V/mm). The experiment results validate the prediction that the relaxor-based materials with the critical composition for the relaxer state will have the highest piezoelectric susceptibility. (C) 2004 Elsevier B.V. All rights reserved.